The Analysis of Speech Acts in “English for Nusantara“ Textbook - Andrian Nuriza Johan; Januarius Mujiyanto; Sri Wuli Fitriati; Rudi Hartono (Universitas Negeri Semarang, 2022)
In cross-cultural communication, pragmatic skill is extremely important. In pragmatics, speech acts are considered